Implementation of Leadership Asta Brata in The Education System at Taruna Mandara High School - Tirtayasa, I Gusti Putu; Sudiana, I Gusti Ngurah; Putrawan, I Nyoman Alit (PT. Hafasy Dwi Nawasena, 2025)
This study aims to analyze the implementation of a leadership system based on Asta Brata in character education at Taruna Mandara High School. Asta Brata Hindu philosophy that includes eight principles of leadership inspired by the attributes of the gods, such as justice (Surya Brata), gentleness (Candra Brata), and responsibility (Baruna Brata). The research method used is qualitative with a case study approach, involving observation, in-depth interviews, and document analysis. The results of the study indicate that the application of Asta Brata successfully formed the character of students who are disciplined, tolerant, have integrity, and have leadership. These values are internalized through personality training, character assessment, and the role model of educators. However, challenges such as differences in student backgrounds, lack of in-depth understanding of the philosophy Asta Brata, and the influence of the external environment hinders the optimization of this system. The implications of this study emphasize the importance of integrating local wisdom into modern education to build a generation that is not only academically intelligent but also has strong character. Recommendations include more intensive teacher training, more creative learning approaches, and strengthening collaboration between schools, families, and communities. Thus, Asta Brata can be a model of relevant and sustainable character education in the era of globalization.